Verkehrsentwicklung in der südlichen Euroregion Oberrhein. Eine Bilanz 1908 bis 2008. - Schröder, Ernst-Jürgen (DVV Media Group, 2009)
Die "RegioTriRhena" im Dreiländereck am Oberrhein liegende Raumschaft bildet mit dem Rhein einen strategisch wichtigen Transitkorridor im europäischen Süd-Nord-Verkehr. Das wachsende Güteraufkommen stellt der Region neue Anforderungen. Viergleisiger Aus- und Neubau der Hauptmagistralen zur Vergrößerung ihrer Frachtkapazitäten und Marktzugang zum europäischen Schienennetz sind Garanten einer modalen Verlagerung und damit einer nachhaltigen Bewältigung wachsender Güterverkehrsmengen. Entscheidender Schwachpunkt bleibt die zu schwache Einbeziehung des Rheins als Verkehrsträger und die schwache faktische Intermodalität.

The spot where three countries meet, is located in the southern "EuroRegion" (Upper Rhine Region), with the river Rhine serving as a natural transport trunk route. Over the last one hundred years, the region has advanced to a strategically highly important transit corridor for European traffic moving south to north while also evolving as the focus of a number of freight haulage trunk routes in Central Europe. The liberalized and deregulated public local rail transport has led to some rather attractive transport services being offered in line with local mobility requirements, even fostering a revival of this transport sector. To make sure that the Upper Rhine Region will in future meet the growing mobility it requirements without any constraints, and not emerge as a large-area bottleneck for freight haulage, its transport infrastructure will have to be developed through trans-border synchronization and coordination. An increase in freight capacity by way of expanding and constructing four-track rail trunk routes, coupled with enhanced market access to Europe's rail network, will serve as a guarantee for modal movement and the ability to cope adequately with growing freight traffic volumes. The inadequate integration of the river Rhine as a means of transport, and the generally weak status of present-day inter-modality, appear to remain the weak points.
Traffic development in the southern "EuroRegion" (Upper Rhine Region).
Keywords: Verkehr; Verkehrsentwicklung; Straßenverkehr; Eisenbahnverkehr; Verkehrsnetz; Güterverkehr; Verkehrsaufkommen; Verkehrsinfrastruktur; Verkehrsmarkt; Transitverkehr; Intermodalität